2012
DOI: 10.1038/leu.2012.343
|View full text |Cite
|
Sign up to set email alerts
|

MLL–AF9-mediated immortalization of human hematopoietic cells along different lineages changes during ontogeny

Abstract: The MLL-AF9 fusion gene is associated with aggressive leukemias of both the myeloid and lymphoid lineage in infants, whereas in adults, this translocation is mainly associated with acute myeloid leukemia. These observations suggest that differences exist between fetal and adult tissues in terms of the 'cell of origin' from which the leukemia develops. Here we show that depending on extrinsic cues, human neonatal CD34(+) cells are readily immortalized along either the myeloid or lymphoid lineage upon MLL-AF9 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
98
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 49 publications
7
98
0
Order By: Relevance
“…In the majority of cases acute lymphoblastic leukaemia developed, but one leukaemia shows mixed myeloid and lymphoid lineage. Transformed CB cells also retained a gene expression signature similar to normal neonatal HSCs [55]. While CB is not an exact surrogate for paediatric BM, this study provides and supports the conceptual basis that AML arising in a young and old cell may be very different.…”
Section: Preclinical Evidence Linking Ontogeny With Disease Phenotypesupporting
confidence: 48%
“…In the majority of cases acute lymphoblastic leukaemia developed, but one leukaemia shows mixed myeloid and lymphoid lineage. Transformed CB cells also retained a gene expression signature similar to normal neonatal HSCs [55]. While CB is not an exact surrogate for paediatric BM, this study provides and supports the conceptual basis that AML arising in a young and old cell may be very different.…”
Section: Preclinical Evidence Linking Ontogeny With Disease Phenotypesupporting
confidence: 48%
“…In the MLL-AF9 knock-in mouse model, FL HSPCs exhibit increased latency and induce leukemias expressing both myeloid and lymphoid markers. 5 In contrast, 6 Although the lineage differences in leukemias from FL and CB HSPCs vs adult HSPCs are thought to reflect cell-of-origin differences between MLL-AF9 1 leukemia in infants and adults, 7 it is not clear whether Id1 participates in determining these lineage differences because the MLL-AF9 retroviral model used in these studies gives rise exclusively to AML. Nonetheless, consistent with the predictions made by these mouse experiments regarding the importance of Id1 expression in infant vs adult-type leukemia, MLL-AF9 1 leukemias from patients age of #3 years express higher levels of Id1 mRNA than patients .3 years of age.…”
mentioning
confidence: 77%
“…JAKV617F is an acquired mutation that occurs within the human population, producing a constitutively active Jak2 that drives the formation of myeloproliferative neoplasms (MPNs). [5][6][7][8][9] The JAKV617F mouse model used in this study, which expresses JAKV617F under the regulatory control of the endogenous Jak2 locus, results in the onset of erythrocytosis and thrombocytosis within a number of weeks 10 and can be effectively transferred via bone marrow transplantation. 10 Mascarenhas et al found that if HSCs from the E11.5 AGM region were used as donor material, the expected pathology did not develop (no evidence of erythrocytosis or thrombocytosis was detected over a prolonged period of time and across 2 rounds of transplantation) and the DNA damage that characterizes adult JAKV617F cells was also absent.…”
mentioning
confidence: 99%
“…It was found that the MLL-AF9 fusion gene, which is predominantly associated with myeloid leukaemias, was able to immortalize this cell type. These cells are still able to differentiate either to the myeloid or to the lymphoid lineage [50].…”
Section: Targeted Immortalization Of Specific Cell Typesmentioning
confidence: 99%